Comparing cityparks and cemeteries: Which habitat better supports urban bird communities? - Nur Muhammad Firmansyah; Ratna Komala; Eka Putri Azrai; Elsa Lisanti; Agung Sedayu (Bioma, 2025)
Urban birds represent the group of organisms adapted to environments characterized by close proximity to human activity. However, disturbances often displacing them to less disturbed habitats. In Jakarta, city parks and cemeteries serve as relatively low-activity green spaces that provide potential refugia for avian communities, thus hold conservation value. This study investigated bird and vegetation diversity in these two types of urban green open spaces (GOS) and examined their relationships the vegetation diversity. Surveys were conducted in four city parks and four cemeteries in circular plots. Results indicated that bird diversity in city parks was moderate, while tree and non-tree diversity ranged from low to moderate. In cemeteries, bird, tree, and non-tree diversity were consistently low to moderate. It is a positive correlation between tree diversity and bird diversity, and a negative correlation between non-tree diversity and bird diversity, though both relationships were not strong. It is also revealed that bird diversity in both city parks and cemeteries differ markedly. These findings highlight the ecological role of urban green spaces in supporting avian diversity and emphasize the importance of vegetation structure in shaping bird communities within highly urbanized landscapes.